Оценка неопределенности измерения физико-химических показателей качества и безопасности подсолнечного масла. - Захаров, И. П.; Чунихина, Т. В.; Папченко, В. Ю. (Харківський університет повітряних сил, 2018)
Techno-chemical control is very important in the food industry. Nowadays Ukraine is a leader among world countries – exporters of the sunflower-seed oil. The main requirements to the sunflower-seed oil are requirements to the parameters the quality and the safety. Technical control is carried out by using laboratory methods for determining the quality and the safety of products. These methods are divided into the physical, chemical, physical-chemical and biological. In this work five parameters of the quality and the safety of the sunflower-seed oil were investigated in this work for an establishment of accordance the requirements of actual regulation documents. The task of the work was the estimation of the uncertainty of measurements with using the physical-chemical methods. These methods were realized by the means of the measuring technique with their own measuring errors. The measurements of the check parameters were done at the reference conditions, the additional errors were absent. The results of the multiple measurements were used to determine the uncertainty of the measurements of type A, the passport date of the devices – to determine the uncertainty of the measurements of type B. The example of the calculation of the uncertainty of measurement of the one of the parameters of the quality and the safety (the acid value) was given. The accuracy of measurement of this parameter is . Therefore, the uncertainty of the measurement of the parameters of the quality and the safety of the sunflower-seed oil was determined.
Keywords: sunflower-seed oil; parameters the quality and the safety; the physical-chemical methods; uncertainty of measurement.; parallel experiments